Expression of reverse transcriptase from feline immunodeficiency virus in Escherichia coli. - North, T W (1994)
Reverse transcriptase from feline immunodeficiency virus (FIV) has been cloned and expressed in Escherichia coli. We have purified this recombinant enzyme and shown that it is a 66-kDa protein that is indistinguishable from virion-derived FIV reverse transcriptase in sensitivity to the 5'-triphosphates of 3'-azido-3'-deoxythymidine and the four 2',3'-dideoxynucleosides. The availability of large quantities of the FIV reverse transcriptase will allow more detailed physical and pharmacological studies.